IMPACT OF OPERATIONAL COSTS OF OPERATIONAL INCOME (BOPO), CAPITAL CAPABILITY RATIO AND MUSYARAKAH FINANCING ON THE PROFITABILITY OF SHARIA COMMERCIAL BANKS 2016-2021 - Anis Kuraeni; Fil Isnaeni (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This research seeks to reveal the relationship between operating costs of operating income, the ratio of capital adequacy and musyarakah financing to the profitability of Islamic/Sharia commercial banks. The independent variables used in this study are operating income operating costs (BOPO), Capital Adequacy Ratio (CAR), Musyarakah Financing and the dependent variables used in this study are the profitability value of Islamic commercial banks. The method used in this study is a quantitative method where the data is in the form of a report officially published by the Financial Services Authority (OJK). From the results of the processing data, it was discovered that there was a relationship and contribution of independent variables to dependent variables, this was seen from the Coefficient of Determination Test with a value of 66%, hence operating costs of operating income, capital adequacy ratio and musyarakah financing  on profitability is seen from the results of the T test and F test where both have a value of < 0.05, which means that the variables BOPO, Capital Adequacy and Musyarakah  Financing simultaneously or separately have the same results, namely inter-mediated and related.